Making local self-government in rural India work: Old tradition and new challenges - Datta, Prabhat Kumar (2013)
Conceptually, while local government can be regarded as the offspring of administrative decentralisation, local selfgovernment is the manifestation of political decentralisation the significance of which received a lot of attention in the 19th Century. The constituionalisation of the local governance has changed the legal status of the Panchayati Raj system. Panchayati Raj is no longer an idea but a practice. The constitutional provisions have laid the foundation stone of local government the superstructures of which have to be built up for which what is urgently needed is spontaneous initiative on the part of the people. There is some ray of hope following the rise and growth of the civil society organisation in India working for democratisation of governance. - Reproduced.
Keywords: Panchayat - India; decentralization - India; Local government - India; Local government